In situ synthesis and photocatalytic hydrogen production of plate‐like Cu‐doped TiO2 polycrystal with crystal‐axis orientation. (1st August 2020) - Lei, Ji; Wang, Xing; Zhou, Jinhong; Kong, Xingang
Abstract : The Cu‐doped TiO2 plate‐like particle was synthesised via using the layered H1.07 Ti1.73 O4 ·H2 O (HTO) plate‐like particle as a precursor. The Cu‐doped TiO2 particle consists of nanocrystals and holes, and these nanocrystals are oriented at [ 1 ¯ 1 ¯ 1 ]‐crystal‐axis direction. Firstly, the HTO particle was treated in a copper acetate solution, forming Cu 2+ ‐exchanged HTO plate‐like particles. And then Cu 2+ ‐exchanged HTO in situ transformed into Cu‐doped TiO2 via heat‐treating and further acid washing. The Cu‐doped TiO2 particle has a stronger absorption in the visible light region of 400–800 nm and the visible photocatalytic H2 production activity.